Modeling of fibrous tow transmission considering residual strain and friction. Issue 17 (September 2021) - Che, Jinkai; Zhang, Zengmeng; Hou, Jiaoyi; Chen, Yinglong; Gong, Yongjun
This study established a mechanical model based on the mechanical properties of fibrous tows and their force of interaction with spools. The proposed model not only describes the hysteresis, nonlinear elastic, and viscoelastic stress components, but also analyzes the effect of residual strain on aramid fiber mechanical properties. Moreover, the effect of the interaction force between the fiber and spool on the transmission accuracy should be considered. Contrary to the conventional view, hysteresis is caused not only by internal sliding among molecules and molecular chains but also by friction between the fibers and spools. To assess this effect, several monotonous and cyclic tensile tests were conducted, with the results showing that the maximum relative error of the mechanical model did not exceed 5%. The proposed mechanical model can help designers determine effective carrying ranges and predict the fiber mechanical behavior, thereby laying a foundation for achieving nonlinear control of the fibrous tow transferring load.